Does Investment and Energy Infrastructure Influence Convergence in Sumatra Island, Indonesia? - Hidayat, Muhammad; Bachtiar, Nasri; Sjafrizal, Sjafrizal; Primayesa, Elvina (International Journal of Energy Economics and Policy, 2022)
This research aims to prove the existence of a convergence process and analyse the effect of investment and energy infrastructure on the convergence process on Sumatra Island by including the element of space to understand spatial convergence better. The dataset used in panel data consists of 154 regions (district/municipality) from 2010 to 2020. The analytical tools used with a spatial econometric approach consist of Spatial Autoregressive (SAR) and Spatial Error Model (SEM). The results of the convergence test prove that there is convergence in both absolute and conditional convergence, and there is a difference in the speed of convergence for the two equations. Meanwhile, the results of the spatial approach state that there are spatial dependencies so that neighbouring regions influence the region. The estimation results of conditional β-convergence reveal that investment and government spending in infrastructure has a positive and significant effect, in contrast to energy infrastructure, which has a negative and significant relationship, and only human capital is not significant to the convergence process in Sumatra.